Use of a Population Pharmacokinetic Approach for the Clinical Development of a Fixed‐Dose Subcutaneous Formulation of Trastuzumab. (2nd January 2014) - Hourcade‐Potelleret, F; Lemenuel‐Diot, A; McIntyre, C; Brewster, M; Lum, B; Bittner, B
Abstract : A new subcutaneous (s.c.) trastuzumab formulation provides savings in terms of time and is preferred by patients and health care professionals relative to standard intravenous (i.v.) administration due to simpler and more rapid administration (2–5 minutes). Selection of the s.c. dose was based on a pharmacokinetic bridging approach that aimed to achieve noninferior trastuzumab serum trough concentrations ( C trough ) vs. reference i.v. administration. Using population modeling and simulation, we showed that a fixed 600‐mg trastuzumab s.c. dose, administered thrice‐weekly (Q3W) without a loading dose, would provide C trough (predose Cycle 8) and area under the time–concentration curve (AUC0–21 days, Cycle 7) at least as high as Q3W i.v. administration. The model was retrospectively validated using observed pharmacokinetic data from an independent phase III study of (neo)adjuvant trastuzumab (HannaH). These results provide a strong pharmacokinetic rationale for the trastuzumab s.c. 600‐mg fixed dose, supported by the noninferior efficacy of this regimen vs. reference i.v. administration. CPT Pharmacometrics Syst. Pharmacol . (2014) 3, e87; doi:10.1038/psp.2013.63 ; advance online publication 2 January 2014